1998
DOI: 10.3354/meps170215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of parasitized and hyperparasitized crabs near South Georgia

Abstract: This study identifies sources of variation in the prevalences of parasitized and hyperparasitized Paralomis spinosissima, a lithodid found around South Georgia. The parasite is Briarosaccus callosus, a rhizocephalan; the hyperparasite is an undescribed linopsinine. Generalized additive models were used to model data collected dunng 1992 and 1995. Parasites were less prevalent on female crabs and most prevalent in submarine canyons The former effect may be due to sex-specific differences in gill cleaning behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…We found a higher prevalence of parasitism in females, but previous studies of lithodids have reported conflicting results on the subject of gender bias (Watters 1998;Poltev 2008). The prevalence of parasites may vary by location (Otto and MacIntosh 1996;Lovrich et al 2004); compared with the 14% of P. birsteini infected by B. callosus in the present study, rates of parasitism ranging from \1% to as high as 75% have been reported for lithodid populations globally (Hawkes et al 1985;Hoggarth 1990;Watters 1998;Anosov et al 2014). Consequently, the prevalence could be different in other P. birsteini populations.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…We found a higher prevalence of parasitism in females, but previous studies of lithodids have reported conflicting results on the subject of gender bias (Watters 1998;Poltev 2008). The prevalence of parasites may vary by location (Otto and MacIntosh 1996;Lovrich et al 2004); compared with the 14% of P. birsteini infected by B. callosus in the present study, rates of parasitism ranging from \1% to as high as 75% have been reported for lithodid populations globally (Hawkes et al 1985;Hoggarth 1990;Watters 1998;Anosov et al 2014). Consequently, the prevalence could be different in other P. birsteini populations.…”
Section: Discussioncontrasting
confidence: 64%
“…The prevalence of B. callosus varies as a function of size in lithodids, with higher rates of infestation observed in smaller individuals (Lovrich et al 2004). The parasite has also been shown to limit crustacean growth (Hawkes et al 1987;Watters 1998) which enhances the bias in infestation toward smaller sizes of hosts. In the present study, a similar relationship was seen in females, with B. callosus found only in the smallest-four females (CL 52.3-60.6 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this decrease in parasite abundance was due to parasite-dependent mortality (Hypothesis 3). Such a dome-shaped curve of parasite abundance (or prevalence) in its host in relation with cohort age has already been utilised as a parasitedependent mortality index in other host -parasite systems, mainly with first intermediate hosts (Bowers 1969, Schmidt & Fried 1997, Rantanen et al 1998, Watters 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported the occurrence of isopod hyperparasites in lithodids infested by the rhizocephalan Briarosaccus callosus from the Crozet Islands, South Georgia Islands and Canadian Atlantic waters, but none of them identified these specimens (Boschma 1962, Arnaud & Do-Chi 1977, Pohle 1992a,b, Otto & MacIntosh 1996, Watters 1998. While examining commercial catches of the false king crab Paralomis granulosa, taken from the Beagle Channel from 1996 to 1998, we found some B. callosus infested by 1 or more isopod epicarid each.…”
Section: Introductionmentioning
confidence: 96%
“…In the southern hemisphere, B. callosus was found infesting Lithodes santolla, Paralomis granulosa, and P. spinosissima. The infested specimens of P. granulosa and L. santolla were collected in the Strait of Magellan, Beagle Channel and Malvinas (Falkland) Islands (Boschma 1962, Stuardo & Solís 1963, Campodonico et al 1983, Vinuesa 1989, Hoggarth 1990, Roccatagliata & Lovrich 1999, whereas those of P. spinosissima were found exclusively in the South Georgia Islands area (Basson 1994, Otto & MacIntosh 1996, Watters 1998. Otto & MacIntosh (1996) suggested that infested crabs from the South Georgia Islands identified by Boschma (1962) as Lithodes antarcticus (= L. santolla) probably belong to P. spinosissima.…”
Section: Introductionmentioning
confidence: 99%